Hydrogen-motivated electrolysis of sodium carbonate with extremely low cell voltage. Issue 29 (28th February 2018) - Liu, Jia; Xiong, Hailang; Tong, Siyuan; Tang, Yang; Chen, Yongmei; Sun, Yanzhi; Yang, Xiaojin; Wan, Pingyu; Khan, Zia Ul Haq
Abstract : Hydrogen-motivated electrolysis of Na2 CO3 for energy-saving production of NaOH and CO2 /NaHCO3 is realized by using HOR to insert H + into the anolyte and by using HER to extract H + out of the catholyte. Abstract : Hydrogen-motivated electrolysis of Na2 CO3 for energy-saving production of NaOH and CO2 /NaHCO3 is realized by the hydrogen oxidation reaction to insert proton into anolyte and the hydrogen evolution reaction to extract proton out of catholyte. Electrolytic voltage at 100 mA cm −2 is as low as 0.88 V; this voltage is only 35% of the voltage used in the traditional electrolysis.